Pengembangan Kemampuan Emosional Anak Usia Dini Melalui Permainan Tradisional Congklak: DEVELOPMENT OF EARLY CHILDREN'S EMOTIONAL ABILITY THROUGH CONGKLAK'S TRADITIONAL GAMES - AISYAH PUTRI RAMBE; DINIL ARIFAH NASUTION; RHEINA MEISYAH SIREGAR; KHADIJAH KHADIJAH; Hafifah (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
This study sought to determine whether familiar congklak games influence how children interact with one another to enhance their social and emotional skills. A type of qualitative research known as descriptive research describes the actual situation in the field at the time of the study. The collected data are analyzed narratively, or by assembling the events' descriptions into a story. The study included four to five-year-olds from Rantauprapat, Kel, who lived in the Port Road neighborhood. Rantau Utara District, Padang Matinggi District, and Labuhan Batu District. Observation was used to collect data in this study. The study found that playing congklak in the stone port had little effect on how children between the ages of 4 and 5 developed their emotions. Additionally, made-up activities are based on games that young children can play.